2009
DOI: 10.1007/s00421-009-1000-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical activity: a critical appraisal

Abstract: Assessment of physical activity in a free-living environment is important for understanding relations between physical activity and health and determining the effectiveness of interventions. Techniques include behavioral observation, questionnaires in the form of diaries, recall questionnaires and interviews, and physiological markers like heart rate, calorimetry, and motion sensors. The doubly labeled water method has become the gold standard for the validation of field methods of assessing physical activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
290
0
22

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(314 citation statements)
references
References 42 publications
2
290
0
22
Order By: Relevance
“…Snack consumption and body weight M Viskaal -van Dongen et al needed to confirm this, using, for example, doubly labeled water, 24 this observation suggests that subjects mainly compensated by adapting their energy intake. This is supported by previous studies showing that total energy expenditure is not affected by meal frequency, which suggests that any effects of snack consumption on body weight are mediated through energy intake and not energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Snack consumption and body weight M Viskaal -van Dongen et al needed to confirm this, using, for example, doubly labeled water, 24 this observation suggests that subjects mainly compensated by adapting their energy intake. This is supported by previous studies showing that total energy expenditure is not affected by meal frequency, which suggests that any effects of snack consumption on body weight are mediated through energy intake and not energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the short EPIC questionnaire was considered to be an adequate activityranking instrument (Westerterp, 2009 * The order of the category pairings (blocks 3, 4, 6, and 7) will be counterbalanced. Rudolph and colleagues found a strong effect size of d − 0.70 suggesting strong weight bias on hiring outcomes (for further interpretation, see Rudolph et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…7 Another method is objective monitoring through, for example, accelerometers. 8,9 Females from the general population tend to overreport amount of physical activity when comparing to objective assessment. 10 To our knowledge, no previous study has compared self-reported and objectively assessed physical activity in patients with ED.…”
Section: Introductionmentioning
confidence: 99%